Parasitic energy savings in engines using nanolubricants - Saidur, Rahman; Lai, Y.K. (Energy Education Science and Technology Part a-Energy Science and Research, 2010)
The engine friction is one of the causes of power losses found in the operation of a vehicle. This friction is caused by the relative motion of moving components in an engine. As significant portion of an engine's generated power is used at low loads, a reduction in an engine friction would provide significant amount of fuel savings. This study focused on the possible usage of nano-technology in enhancing lubricant properties to achieve a lower friction coefficient. The study also estimated the fraction of energy lost due to friction in an engine. In this study, it has been found that even with the modest estimation, a net fuel savings of 4 can be achieved with the application of nano-additives in lubricants.